2022
DOI: 10.1002/dmrr.3554
|View full text |Cite
|
Sign up to set email alerts
|

12(S)‐hydroxyeicosatetraenoic acid is significantly increased in diabetic kidney disease and associated with renal function decline

Abstract: Aims: 12(S)-hydroxyeicosatetraenoic (12(S)-HETE), an alternate arachidonic acid metabolite, has been recently examined in metabolic disease. However, the role of 12(S)-HETE in diabetic kidney disease (DKD) remains unclear. We studied for the first time the relationship of serum 12(S)-HETE and DKD and renal function parameters in a Chinese population. Materials and Methods:We recruited 275 subjects who were diagnosed with type 2 diabetes (T2DM) for more than 10 years, including 149 DKD patients and 126 T2DM pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…12(S)-HETE was also moderately correlated with ACR and uAER and had a great prediction of DKD. Our results are consistent with the previous study that revealed the association between serum 12(S)-HETE level and diabetic kidney disease [14]. The slight decrease of serum 12(S)-HETE in patients of G3a ~ G3b and A3 groups may suggest a greater prediction role of 12(S)-HETE at the early stage of DKD which needs further studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…12(S)-HETE was also moderately correlated with ACR and uAER and had a great prediction of DKD. Our results are consistent with the previous study that revealed the association between serum 12(S)-HETE level and diabetic kidney disease [14]. The slight decrease of serum 12(S)-HETE in patients of G3a ~ G3b and A3 groups may suggest a greater prediction role of 12(S)-HETE at the early stage of DKD which needs further studies.…”
Section: Discussionsupporting
confidence: 92%
“…In ammation has long been considered as a pivotal factor in dyslipidemia, so our results might provide a clue for 12(S)-HETE promoting the dyslipidemia in the development of DKD through in ammatory pathways. In previous clinical studies, 12(S)-HETE was identi ed as an important biomarker to predict and diagnose the onset and progression of DKD and 12-HETE/PGI2 ratio was showed to be correlated with albuminuria in diabetes mellitus [7,14]. These clinical data and our results were consistent with preclinical ndings of 12(S)-HETE in DKD and provided a potential target of 12(S)-HETE in preventing the development of DKD, which can help us demonstrate the undergoing pathogenesis in T2DM patients who develop DKD even with intensive glycemic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation